Manajemen Perkandangan Ayam Petelur Fase Grower pada PT. Inti Tani Satwa: Management of Laying Hens Cages in Grower Phase at PT. Inti Tani Satwa - Hasrullah; Suci Ananda; Anas Qurniawan (Anoa: Journal of Animal Husbandry, 2022)
Management is one very important part in a business, especially in housing management. The cage is a building that provides a sense of security and comfort for livestock. The cage is very important because the comfort of the cage will affect the productivity of the poultry. The purpose of cage management is to find out how far a farm provides comfort for livestock in order to achieve good productivity. therefore the research was conducted in the cage of PT. Inti Tani Satwa to see how the housing management is there. This type of research is qualitative. There are two data collected, namely primary data and secondary data. Primary data comes from interviews and observations, while secondary data comes from the SOP/manual of maintenance management, then analyzed by descriptive method. The conclusion of the research is the cage model used at PT. Inti Tani Satwa is an open house model where the direction of the cage stretches from east to west. The equipment used for drinking water uses a nipple, while for the feed, it still uses a manual one. The frequency of feeding is done twice a day, in the morning and afternoon, for drinking water is given ad libitum. Coop maintenance and biosecurity are also applied to the laying hens of PT. Inti Tani Satwa.